Does Digital Financial Literacy Matter for Current and Future Saving Behavior among Rural SME Entrepreneurs? Government Regulations Awareness as a Moderator - MUTYA, Tomasi; M., Ilankadhir (Theoretical and Practical Research in Economic Fields, 2024)
Digital financial literacy (DFL) is a game changer in a digital environment. This study examines the impact of DFL on saving behavior among rural small and medium enterprise (SME) entrepreneurs in a developing country. It also explores the effect of government regulations awareness on the association between current and future saving behavior. The study examined rural SME entrepreneurs in Uganda who engaged in financial transactions through mobile phones and retail financial agents. The study employed purposive and snowball sampling procedures to identify rural SME entrepreneurs. Data from 215 rural SMEs entrepreneurs was obtained and analyzed using structural equation modelling and Hayes PROCESS macro. The results indicated that knowledge of digital financial services and products, digital financial risks and control, and consumer rights and reporting procedures significantly impact SME entrepreneurs’ current saving behavior. The current saving behavior has a significant positive impact on future saving foresight. Government regulations awareness significantly impacts the indirect path of DFL on future saving foresight via current saving. This study provides insights for academicians, policymakers, owners of rural SMEs, policymakers, and financial institutions’ top and middle-level managers interested in improving the financial situation of rural SMEs in developing countries. The originality of this study is established in rural SMEs entrepreneurs' awareness of government regulations in a digital environment that moderates the association between current and future saving behavior with DFL as a primary construct.